2019
DOI: 10.3348/kjr.2018.0615
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automatic Segmentation of Acute Ischemic Lesions on Diffusion-Weighted Imaging Using Convolutional Neural Networks: Comparison with Conventional Algorithms

Abstract: Objective To develop algorithms using convolutional neural networks (CNNs) for automatic segmentation of acute ischemic lesions on diffusion-weighted imaging (DWI) and compare them with conventional algorithms, including a thresholding-based segmentation. Materials and Methods Between September 2005 and August 2015, 429 patients presenting with acute cerebral ischemia (training:validation:test set = 246:89:94) were retrospectively enrolled in this study, which was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Deep learning algorithms have been applied to medical imaging [ 9 ] and have led to an exciting opportunity for data-driven stroke management and guiding the diagnosis of acute ischemic stroke [ 30 , 31 ]. Recently, several studies have used CNN algorithms for application in acute ischemic lesions [ 32 , 33 , 34 , 35 , 36 ] and provided effective tools for automatic lesion segmentation or volume calculation. Other studies have focused on developing a deep learning-based approach for detection or identification of large vessel occlusion from CT angiography [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning algorithms have been applied to medical imaging [ 9 ] and have led to an exciting opportunity for data-driven stroke management and guiding the diagnosis of acute ischemic stroke [ 30 , 31 ]. Recently, several studies have used CNN algorithms for application in acute ischemic lesions [ 32 , 33 , 34 , 35 , 36 ] and provided effective tools for automatic lesion segmentation or volume calculation. Other studies have focused on developing a deep learning-based approach for detection or identification of large vessel occlusion from CT angiography [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion imaging lesion pattern, which provides useful information for early diagnosis of acute ischemic stroke, has been reported to be closely related to the stroke subtype 8,9 . To diagnose acute ischemic stroke in brain MRI images, various deep learning algorithms based on convolutional neural networks (CNNs) have been proposed [10][11][12][13][14][15][16][17][18][19][20][21] . These studies have shown that deep learning can detect stroke lesions more accurately than traditional machine learning techniques and can extract meaningful features for severity evaluation or prognosis prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Guerrero et al (15) proposed a CNN architecture (uResNet) to segment and differentiate WMH and stroke lesions by combining T1 and FLAIR images. Woo et al (16) compared CNN with conventional algorithms in segmenting AIL on DWI images. Duong et al (17) adapted a 3D U-net architecture for automatic segmentation of lesions on FLAIR images.…”
Section: Introductionmentioning
confidence: 99%